Influence of drop weight geometry and interlayer on impact behavior of RC beams - Li, H.; Chen, Wensu; Hao, Hong (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 Elsevier Ltd A number of drop weight tests on reinforced concrete (RC) beams have been reported in literature. These tests conducted by different researchers used drop weight of different geometries. Some researchers also placed an interlayer between the drop weight and RC beam in the tests, while others directly dropped the weight on the beam. These different testing configurations surely affect the testing results. However, only very limited studies have been conducted to investigate their effects on the impact behavior of RC beams. In this study, the influence of drop weight geometry and interlayer on the impact behavior of RC beams is numerically investigated by using explicit finite element code LS-DYNA. The numerical models of RC beams subjected to drop weigh impact are verified by available testing data. With the calibrated model, the responses of RC beams impacted by five commonly used drop weights are analyzed and discussed. The effect of steel plate or rubber pad interlayer between drop weight and RC beam is also investigated. It is found that both the drop weight geometry and interlayer property significantly affect the impact loading profile and the failure mode of RC beams. Furthermore, although most drop-weight tests assume vertical impact, small inclination angles of drop weight impacting on beams might occur. The influence of this small testing error on testing results is also investigated.